The current state of the production of wall ceramic products in Kazakhstan - Kaliyeva Жанар; Ajdarlinov Чингиз (Рroblems of engineering and professional education, 2023)
Production of products from ceramics is among the most dynamically developing branches of the Kazakhstan economy. The republic has sufficient stocks of various raw materials for production of construction materials, including for production of construction pottery. There are 870 fields of clays which general stocks are estimated at 1,3 million cubic meters, for production of a brick in Kazakhstan. Meanwhile fireresistant bricks are imported.